Increasing Sleep Health Awareness in Pediatric Settings: Creating Opportunities for Generating a More Sleep-literate Health Care Workforce - Sarah Blunden; Perran Boran (Çocuk Dergisi)
Sleep health is one of the major contributors to mental and physical health and as such should be an essential component of informed community and policy conversations around health. Non-physiological sleep problems are commonly referred to as Behavioral Sleep Problems (BSP) and include difficulties initiating sleep alone, bedtime resistance, difficulties re-initiating sleep after normally occurring overnight waking (requiring parental assistance to re-settle) and/or early morning wakening. BSP affects up to 40% of children under two years of age. Despite the high prevalence and impact of sleep disturbance, training and education curricula for pediatric medical and allied health professions include little information or awareness building about sleep, particularly in strategies to ameliorate sleep for children and their families. An evident need to train health professionals working with children in evidence-based pediatric behavioral sleep care is emerging. A recent partnership between Turkey and Australia has tackled this problem. By developing a scientific collaborative network between the two countries and using existing evidence-based methods, clinical information was shared between health professional workforces in these two countries as effective ways of translating knowledge in pediatric sleep interventions. Systematic training of primary and tertiary medical and allied health professionals must be considered as standard practice in tertiary education settings.